Effects of pre-activation with variable intra-repetition resistance on throwing velocity in female handball players: a methodological proposal - Martínez-García, D.; Rodríguez-Perea, Á.; Huerta-Ojeda, Á.; Jerez-Mayorga, D.; Aguilar-Martínez, D.; Chirosa-Rios, I.; Ruiz-Fuentes, P.; Chirosa-Rios, L. J. (Journal of Human Kinetics, 2021)
The purpose of this study was to investigate the acute effect of pre-activation with Variable Intra-Repetition Resistance and isometry on the overhead throwing velocity in handball players. Fourteen female handball players took part in the study (age: 21.2 ± 2.7 years, experience: 10.9 ± 3.5 years). For Post-Activation Potentiation, two preactivation methods were used: (I) Variable Intra-Repetition Resistance: 1 x 5 maximum repetitions at an initial velocity of 0.6 m·s-1 and a final velocity of 0.9 m·s-1; (II) Isometry: 1 x 5 s of maximum voluntary isometric contraction. Both methods were "standing unilateral bench presses" with the dominant arm, using a functional electromechanical dynamometer. The variable analysed was the mean of the three overhead throws. Ball velocity was measured with a radar (Stalker ATS). The statistical analysis was performed using ANOVA with repeated measures. No significant differences were found for either method (variable resistance intra-repetition: p = 0.194, isometry: p = 0.596). Regarding the individual responses, the analysis showed that 86% of the sample increased throwing velocity with the variable resistance intra-repetition method, while 93% of the sample increased throwing velocity with the isometric method. Both the variable intra-repetition resistance and isometric methods show improvements in ball velocity in female handball players. However, the authors recommend checking individual responses, since the results obtained were influenced by the short rest interval between the pre-activation and the experimental sets.